Avoiding monetary loss: A human habenula functional MRI ultra-high field study. (September 2021) - Weidacker, Kathrin; Kim, Seung-Goo; Nord, Camilla L.; Rua, Catarina; Rodgers, Christopher T.; Voon, Valerie
Abstract: A number of convergent human neuroimaging and animal studies suggest that habenula neurons fire in anticipation of non-rewarding outcomes, and suppress their firing in anticipation of rewarding outcomes. This normative function of the habenula appears disrupted in depression, and may be critical to the anti-depressant effects of ketamine. However, studying habenula functionality in humans using standard 3 T MRI is inherently limited by its small size. We employed ultra-high field (7 T) fMRI to investigate habenular activity in eighteen healthy volunteers during a Monetary Incentive Delay Task, focussing on loss avoidance, monetary loss and neutral events. We assessed neural activation in the field of view (FOV) in addition to ROI-based habenula-specific activity and generalized task-dependent functional connectivity. Whole FOV results indicated substantial neural differences between monetary loss and neutral outcomes, as well as between loss avoidance and neutral outcomes. Habenula-specific analyses showed bilateral deactivation during loss avoidance, compared to other outcomes. This first investigation into the habenula's role during loss avoidance revealed that the left habenula further differentiated between loss avoidance and monetary loss. Functional connectivity between the right habenula and the ipsilateral hippocampus and subcallosal cingulate (regions implicated in memory and depression pathophysiology) was enhanced when anticipating potential losses compared to anticipating neutral outcomes. Our findings suggest that the human habenula responds most strongly to outcomes of loss avoidance when compared to neutral and monetary losses, suggesting a role for the habenula in both reward and aversive processing. This has critical relevance to understanding the pathophysiology of habenula function in mood and other neuropsychiatric disorders, as well as the mechanism of action of habenula-targeting antidepressants such as ketamine.